Thrombogram: case report of pseudothrombocytopenia - Bruno Miguel B. Costa; Maria C. Vellés; Maria Mariana F. B. Viana; Ana Conceição M. Pereira; Susana Catarina P. Rocha; Liliana P. Rocha; Vera Monica R. P. Moreira
ABSTRACT The thrombogram is one of the components of the blood count that includes platelet quantification and evaluation. The presence of laboratory artifacts, such as incorrect platelet counts by autoanalyzers, can lead to pseudothrombocytopenia, which is responsible for 15% to 30% of the cases of isolated thrombocytopenia observed in laboratory routine. Pseudothrombocytopenia induced by the anticoagulant ethylenediaminetetraacetic acid (EDTA) is one of the most frequent cases in which the presence of anticoagulant in blood samples can cause platelet aggregation or platelet satellitism. Careful observation of the data emitted by autoanalyzers, such as platelet and flag histograms, is crucial. Other procedures, such as checking for clotting in the sample, repeating the sample and viewing a peripheral blood smear, requesting a new sample taken with another type of anticoagulant, such as citrate, are imperative for the confirmation of cases of pseudothrombocytopenia.